Plasma adiponectin is increased in mice selectively bred for high wheel-running activity, but not by wheel running per sé - Vaanholt, L M; Meerlo, P; Garland, Jr, T; Visser, G H; van Dijk, G (Hormone and metabolic research, 2007)
Mice selectively bred for high wheel-running activity (S) have decreased fat content compared to mice from randomly bred control (C) lines. We explored whether this difference was associated with alterations in levels of circulating hormones involved in regulation of food intake and energy balance, and whether alterations were caused by the presence of a running wheel. Plasma levels of leptin, adiponectin, and corticosterone as well as body composition were analyzed in male S mice housed with (+) and without (-) access to running wheels at ages of 10 and 18 months. These levels were compared to those found in C+ mice. Plasma corticosterone did not differ among groups. While plasma leptin levels tended to be lower in S+ mice as compared to S- or C+ mice, these differences were largely attributable to differences in fat content. Adiponectin levels were increased in S mice (+60%) compared to C mice, irrespective of wheel access. High levels of this hormone may be a trait co-segregated in mice bred for high wheel-running activity.